The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1111/j.1365-2222.2007.02679.x
|View full text |Cite
|
Sign up to set email alerts
|

Eczema, atopy and allergen exposure in adults: a population‐based study

Abstract: There is geographical variation in the prevalence of eczema in adults both within and between countries. Although the disease is associated with IgE sensitization, in this study it was not related to mattress mite or cat allergen levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

17
117
2
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(138 citation statements)
references
References 39 publications
17
117
2
2
Order By: Relevance
“…We have found using data from our work that the lifetime clinician{recorded prevalence peaks in younger children mirrored results from a birth cohort, 13 and the prevalence in our older adults was similar to that found in survey data. 7 Although little data on the trend of eczema prevalence exist prior to World War II (1939)(1940)(1941)(1942)(1943)(1944)(1945), the prevalence of eczema increased substantially in the latter half of the 20th century, with eczema in school{aged children being found to increase between the late 1940s and 2000. [14][15][16] In contrast to our results, survey studies (see Box 2 Trends in the epidemiology and prescribing of medication for eczema in England for questions used in surveys) from the period immediately prior (1995-1996 to 2000-2001) 17 and intersecting our study period (1995-1996 to 2002-2003) 6 found only a moderate increase in eczema in children (2-15 years), a decrease in older children (13-14 years) and no increase in adults (aged >15 years) over time.…”
Section: Main Strengths and Limitations Of This Workmentioning
confidence: 99%
See 2 more Smart Citations
“…We have found using data from our work that the lifetime clinician{recorded prevalence peaks in younger children mirrored results from a birth cohort, 13 and the prevalence in our older adults was similar to that found in survey data. 7 Although little data on the trend of eczema prevalence exist prior to World War II (1939)(1940)(1941)(1942)(1943)(1944)(1945), the prevalence of eczema increased substantially in the latter half of the 20th century, with eczema in school{aged children being found to increase between the late 1940s and 2000. [14][15][16] In contrast to our results, survey studies (see Box 2 Trends in the epidemiology and prescribing of medication for eczema in England for questions used in surveys) from the period immediately prior (1995-1996 to 2000-2001) 17 and intersecting our study period (1995-1996 to 2002-2003) 6 found only a moderate increase in eczema in children (2-15 years), a decrease in older children (13-14 years) and no increase in adults (aged >15 years) over time.…”
Section: Main Strengths and Limitations Of This Workmentioning
confidence: 99%
“…Another strength of this study was the use of contemporaneous clinician recording of a diagnosis of eczema as opposed to patient self{reporting of historical diagnoses or symptoms. 6,7 There are a number of limitations related to the use of large routinely collected data from primary care, including the dependence on clinician{ recorded diagnosis of eczema and possible improvements in recording over the study time period. The relatively short time window over which trends were studied is another limitation, but this does also have the advantage of confining analysis to a period during which there were no changes in disease definition or classification.…”
Section: Main Strengths and Limitations Of This Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have suggested the following prevalence: psoriasis 1-8% [2], hidradenitis suppurativa (HS) 0.33-4% [3,4], adult atopic eczema (AE) 0.3-6.2% [5], pimples 3.5% and hand rash 3.3% [6]. Hospital-based studies indicate that skin diseases reduce patients' quality of life (QoL), but the morbidity of these large groups of patients found in the general population is poorly described.…”
Section: Introductionmentioning
confidence: 99%
“…FA caused by fruits, vegetables, tree nuts, peanuts and seafood seem to be most prevalent in adults [9,10,21] . Sensitization may occur directly to food allergens or indirectly through cross-reactivity with aeroallergens.…”
mentioning
confidence: 99%